2016
DOI: 10.1111/jcpt.12349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a transition to more restrictive drug formulary on therapy discontinuation and medication adherence

Abstract: Transition of patients to a more restrictive drug formulary led to modest therapy discontinuation, similarly modest improvements in medication adherence and substantial prescription drug cost savings. As healthcare payors search for ways to control the rapid rise in spending for medications without compromising quality, the Value Formulary can serve as a useful tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Not surprisingly, as patient out-of-pocket costs increase, adherence decreases 6,11,[40][41][42] . Restrictions put in place by commercial health plans limiting quantities or requiring prior authorization for specific classes of drugs, including GLP-1 RAs, may also affect adherence 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, as patient out-of-pocket costs increase, adherence decreases 6,11,[40][41][42] . Restrictions put in place by commercial health plans limiting quantities or requiring prior authorization for specific classes of drugs, including GLP-1 RAs, may also affect adherence 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Some studies have found positive effects of these tools and strategies on pharmacotherapy outcomes. 21,22 Additional research is needed to better understand the effect of state-mandated formularies, inclusive of federal and supplemental rebates that states receive from drug manufacturers. However, we can infer from this study that unintended consequences of decreased drug use and increased costs may result when participating Medicaid plans are unable to leverage utilization management strategies, including MCO managed formularies, to control costs and advocate for appropriate, cost-effective therapy.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Toutefois, le E1 15 39 46 36 53 11 50 35 15 19 42 39 16 55 29 E2 28 36 36 39 46 15 51 35 14 63 29 8 59 32 9 E3 25 40 35 36 46 18 53 31 16 23 38 39 22 39 39 E4 40 39 21 40 48 12 41 34 25 37 44 19 35 46 19 E5 28 43 29 40 54 6 69 24 7 41 49 10 42 44 14 E6 14 35 51 47 42 11 54 36 10 35 43 22 34 42 24 E7 59 35 Ainsi, deux facteurs contribuent à la baisse du niveau d'aisance ; en l'occurrence, il s'agit de la mention du recours à une procédure d'exception ou la demande du médecin de faire signer le formulaire par le pharmacien à sa place. De façon générale, les cliniciens détestent les mesures administratives de contraintes visant à justifier leur conduite clinique [18,19]. De plus, le recours à des ressources non-médicales lors de ces procédures n'offre pas forcément de meilleure issue [20].…”
Section: Discussionunclassified